1148 Narcolepsy with Cataplexy in a Pediatric Patient with a Thalamic Mass: A Case Report - Pietrapiana, Stefano (2024)
Introduction: A female adolescent patient with gradual hypersomnolence. Report of case(s) The patient is a 16-year-old with gradual onset of parasomnias, leg cramps, headaches and history of gastroesophageal reflux, and asthma. Her ferritin was low, and a diagnosis of restless legs was made, the patient was started on oral iron supplements without improvement. Intravenous iron replacement therapy was tried with laboratory improvement (>50 ng/ml) but not clinical. Clonazepam and gabapentin were tried without success. Over time, she developed more tiredness and started to fall asleep in class. A sleep study was done which showed primary snoring without evidence of sleep disorder breathing, PLMD index was 4.4, and REM sleep latency was 120 minutes. The headaches got worse, and she was seen by neurology, MRI showed a hyperintense 6mm rounded lesion on the left side of the thalamus. She started pregabalin and remained stable for almost a year. Sleepiness got worse with sleep attacks. She was sleeping 12-14 hours at night with a 1–2-hour nap in the afternoon. A Multiple sleep latency test (MSLT) showed no evidence of sleep-onset rapid eye movement periods (SOREMPs), and the mean sleep latency was 9.6 minutes. She was diagnosed with primary hypersomnolence. Modafinil and methylphenidate were tried for hypersomnolence and added duloxetine for headaches without improvement. A repeated sleep study and MSLT, showed a mean sleep latency of 4.9 minutes without SOREMPs, Epworth Sleepiness Scale (EPS) of 20. Later she started with jerky legs and tripping/falling in gymnastics practice, diagnosis of narcolepsy with cataplexy was made. Sodium oxybate was started with improvement of hypersomnolence (EPS: 8) and cataplexy. Conclusion: The patient presented with insidious onset of restless legs, migraines, and hypersomnia. In pediatric patients classic narcoleptic symptoms are not always present. Interestingly restless legs and migraines can precede the diagnosis of narcolepsy. Our patient had no SOREMPs on the MSLT on two different occasions but in her last MSLT her mean sleep latency was 4.4 minutes and soon after developed cataplexy. Due to the presence of a thalamic mass, we conclude that this patient has secondary narcolepsy type 1.